THE ROLE OF THE FISHERMEN'S LIBRARY IN INCREASING CHILDREN'S READING INTEREST IN THE AIK GENIT TOURISM AREA, SENTELUK VILLAGE, BATULAYAR DISTRICT - Zaini Mulyadi (JOETAL: Journal of Education, Teaching and Learning, 2025)
This study looks into how fishermen's libraries help boost children's interest in reading in the Aik Genit Tourism Area, Senteluk Village, Batulayar District. It also checks how much children are interested in reading in that area. The study used a qualitative and descriptive method, focusing on kids aged 6 to 12 who visit the Fishermen's Library. To collect data, the researchers used unstructured interviews, observations, and record-keeping. They analyzed the data using multiple sources and methods to get a full picture. The study found that: 1) Fishermen's libraries play several roles in increasing children's reading interest, such as being a place where books and human works are kept, a source of information, a non-formal learning place, and a fun space for relaxation. 2) Children's interest in reading is still low. 3) The library faces challenges in improving reading interest, like having a small budget, not enough books, and the influence of online games. 4) To improve reading interest, the library plans to ask for donations, spread information through pamphlets, offer fun activities like outdoor games and coloring contests, and organize outreach programs.